Optimal Portfolio Formation Using Single Index Model on the IDX80 Index for the Period February 2021 – May 2022 - Istiqomah, Ananda Nadya; Warsini, Sabar (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2022)
The policy of the Central Bank of the United States (US), namely the Fed, in raising its benchmark interest rate, has increased the risk of volatility in global markets and triggered negative sentiment for foreign investors in Indonesia. Foreign investors began to relinquish their ownership up to Rp 3.19 trillion. This caused the risk of falling prices. Therefore, investors need to diversify through the formation of an optimal portfolio to minimize risk and maximize return. This study aims to analyze the formation of the optimal portfolio on the IDX80 index for the period February 2021 - May 2022. This type of research is descriptive using quantitative methods. The sample of this research used a purposive sampling technique. This study uses secondary data with data collection methods, namely documentation and literature study. The data analysis method in this study is a single index model. The results showed that of the 53 stock samples, there were 19 optimal stocks. The expected return portfolio level is 0.20% in one day, while the portfolio risk level is 0.05%.